PROFESI: SEBUAH TINJAUAN ETIS - Andre Ata Ujan (Studia Philosophica et Theologica, 2007)
Profession as a social role in essence requires social responsibility because its actualization is prone to the conflict of interests. This simply means that profession by nature is value laden. Knowledge of ethical values and understanding of moral maxims concerning professional activities are, therefore, of highly significant for every professional for such professional quality can help a professional to serve his/her clients and society at large responsibly. However, such knowledge and understanding may not viable enough to encourage moral conducts. What is required most for a professional to be met is moral integrity, that is, a quality of moral personality that enables him/her to be consistent in behaving ethically. To this extent, the capacity to internalize moral values and to make them to be one’s own moral character is indispensable. Virtue ethics at this point can help a lot to build such a character.